Prestasi Belajar Mahasiswa Asal Kabupaten Lembata NTT di Yogyakarta Ditinjau dari Pengelolaan Diri - Godelfridus M.B Labi & Bimono (LPPM Universitas Proklamasi 45, 2011)
Self-management is the main factor for academic achievement. Higher self-management will address to higher academic achievement. Ninety university students originated from Lembata District NTT and currently study in Yogyakarta participated in this study. Academic achievement as the independent variable was identified based on the documentation method. Student’s self-management as the dependent variable was identified through the self-management scale. The self-management scale constructed from five aspects i.e. goal setting, environmental setting, self-monitoring, selfevaluation, and self-reinforcement. The scale has four alternative answers ranged 1-4 (1 for strongly disagree and 4 for strongly agree). Based on the product moment correlation analysis, it was revealed that student's selfmanagement positively correlated to their academic achievement (r = .584, p<.001).